Three new taxa in Lauraceae from India (Bangladesh Journal of Plant Taxonomy, 2009)
Three new taxa, namely Apollonias arnottii Nees var. beddomei M. Gangop. var. nov., Persea macrantha (Nees) Kosterm. var. brevifolia M. Gangop. var. nov., and Phoebe palghatensis M. Gangop. sp. nov. of the family Lauraceae are described and illustrated from India. Keywords: New taxa; Apollonias; Persea; Phoebe; Lauraceae. DOI: 10.3329/bjpt.v16i2.3926 Bangladesh J. Plant Taxon. 16(2): 141-149, 2009 (December)